Phonological or procedural dyslexia: specific deficit of complex grapheme-to-phoneme conversion - Macoir, Joel; Fossard, Marion; Saint Pierre, Marie Catherine; Auclair-Ouellet, Noemie (My University, 2012)
Phonological dyslexia is a written language disorder characterized by poor reading of nonwords when compared with relatively preserved ability in reading real words. There are two main theoretical proposals to explain this deficit: disruption of phonological processing or disruption to the non lexical reading route affecting the grapheme-to-phoneme conversion rules (GPC). In this study, we report a single-case study of a mild aphasic patient with acquired phonological dyslexia. His ability was unimpaired for reading words as well as in a wide range of tasks requiring the activation and explicit manipulation of phonological representations. He could also read every non word with consistent GPC rules, whilst he was impaired for those with context sensitive conversion rules, a pattern of performance never reported before. The implications of these results for theoretical explanations of phonological dyslexia are discussed, as well as the contribution of the patient's concomitant executive deficits to his performance in reading.
Keywords: reading; phonological dyslexia